Effects of 3,4-Methylenedioxymethamphetamine on Conditioned Fear Extinction and Retention in a Crossover Study in Healthy Subjects - Vizeli, Patrick; Straumann, Isabelle; Duthaler, Urs; Varghese, Nimmy; Eckert, Anne; Paulus, Martin P.; Risbrough, Victoria; Liechti, Matthias E. (Frontiers in Pharmacology, 2022)
3,4-Methylenedioxymethamphetamine (MDMA) has shown initial promise as an adjunct in psychotherapy to treat post-traumatic stress disorder (PTSD). The efficacy and safety have been demonstrated across phase I-III studies. However, the mechanism underlying the potential utility of MDMA to treat PTSD has not yet been thoroughly investigated in humans. Preliminary evidence suggests that MDMA may facilitate fear extinction recall, which may be through the release of oxytocin. To test this hypothesis we examined the efficacy of acute MDMA treatment to enhance fear extinction learning and recall. We used a two-period, double-blind, randomized, placebo-controlled, crossover design in 30 healthy male subjects who received placebo and a single dose of MDMA (125 mg). Fear extinction was tested using two separate Pavlovian fear conditioning paradigms, one using skin conductance response (SCR), the other fear-potentiated startle (FPS) to conditioned cues. MDMA treatment occurred after fear conditioning and 2h before extinction learning. Extinction recall was tested 23h after MDMA intake. Additional outcome measures included subjective effects, emotion recognition task, plasma levels of oxytocin, and pharmacokinetics. Fear conditioning and extinction learning were successful in both fear extinction paradigms (generalized eta-squared [ges] for SCR: .08; FPS: .07). Compared to placebo treatment, MDMA treatment significantly reduced SCRs to the reinforced conditioned stimulus (CS+) during extinction learning (ges=.03) and recall (ges=.06). Intensity of the subjective effects of MDMA (good effect, trust, and openness) during extinction learning negatively correlated with the discrimination between CS+ and the safety stimulus (CS-) during recall. MDMA did not influence FPS to conditioned cues. Oxytocin concentration was increased fourfold on average by MDMA during acute effects but was not associated with fear extinction outcomes. MDMA treatment facilitated rapid fear extinction and retention of extinction as measured by SCR to fear cues, in line with animal studies of MDMA facilitation of extinction. This effect may be limited however to certain forms of learned fear responses, as it was not observed in extinction model using startle reactivity as the outcome. This study provides further evidence for facilitation of extinction with MDMA treatment and suggests this may be a component of its efficacy when paired with psychotherapy.